Differences in IgG Fc Glycosylation Are Associated with Outcome of Pediatric Meningococcal Sepsis - Noortje de Haan (American Society for Microbiology, 2018)
ABSTRACT Pediatric meningococcal sepsis often results in morbidity and/or death, especially in young children. Our understanding of the reasons why young children are more susceptible to both the meningococcal infection itself and a more fulminant course of the disease is limited. Immunoglobulin G (IgG) is involved in the adaptive immune response against meningococcal infections, and its effector functions are highly influenced by the glycan structure attached to the fragment crystallizable (Fc) region. It was hypothesized that IgG Fc glycosylation might be related to the susceptibility and severity of meningococcal sepsis. Because of this, the differences in IgG Fc glycosylation between 60 pediatric meningococcal sepsis patients admitted to the pediatric intensive care unit and 46 age-matched healthy controls were investigated, employing liquid chromatography with mass spectrometric detection of tryptic IgG glycopeptides. In addition, Fc glycosylation profiles were compared between patients with a severe outcome (death or the need for amputation) and a nonsevere outcome. Meningococcal sepsis patients under the age of 4 years showed lower IgG1 fucosylation and higher IgG1 bisection than age-matched healthy controls. This might be a direct effect of the disease; however, it can also be a reflection of previous immunologic challenges and/or a higher susceptibility of these children to develop meningococcal sepsis. Within the young patient group, levels of IgG1 hybrid-type glycans and IgG2/3 sialylation per galactose were associated with illness severity and severe outcome. Future studies in larger groups should explore whether IgG Fc glycosylation could be a reliable predictor for meningococcal sepsis outcome. IMPORTANCE Meningococcal sepsis causes significant mortality and morbidity worldwide, especially in young children. Identification of risk factors for a more fulminant infection would help to decide on appropriate treatment strategies for the individual patients. Immunoglobulin G (IgG) plays an essential role in humoral immune responses and is involved in the adaptive immune response against meningococcal infections. Of great influence on the receptor affinity of IgG is the N-glycan on its fragment crystallizable (Fc) portion. In the present study, we analyzed IgG glycosylation during the fast development of meningococcal sepsis in children, and we were able to identify glycosylation features that are different between meningococcal sepsis patients and healthy controls. These features might be indicative of a higher susceptibility to meningococcal sepsis. In addition, we found glycosylation features in the patients that were associated with illness severity and severe disease outcome, having the potential to serve as a disease outcome predictor.